Mind the Gap: An exploratory investigation of a family learning initiative to develop metacognitive awareness. (June 2017) - Wall, Kate; Burns, Helen; Llewellyn, Anna
Mind the Gap is a family learning project aiming to facilitate intergenerational engagement with learning in schools through the vehicle of a stop-motion animation project. 1 Implicit in the animation process is reflective and strategic thinking that helps to make the process of learning explicit (Learning to Learn: Wall et al.). The animation project takes place in school and targets Year 4 children (aged 8 and 9 years old) and their dads/male guardians. The project is accompanied by staff development in school to promote the same Learning to Learn approaches across curriculum and home/school boundaries. A team of researchers at Durham University is engaged in two projects: first, developing better understanding of the intervention elements and, second, evaluating the impact. This article will focus on data arising from the former and will explore the space for family learning created in the project. We propose that the context of an inherently challenging animation project, which includes schools, parents and children working together in new ways to learn new skills associated with information technology and creative story making, increases the likelihood of dialogue about learning. It opens up the possibility of new relationships between home and school as well as increases the potential for learning-based conversations that could be lifelong and lifewide.